The teacher - McFadden, Freida (2024)
"Something isn't right at Caseham High School. Last year, the school was rocked by scandal: a teacher was accused of having an inappropriate relationship with a student. Now, Addie is a pariah and will do anything to get through the year. More than that, she's desperate to keep the truth from coming to light. Evie, a colleague of the disgraced teacher, is horrified to find Addie in her class. She knows the girl can't be trusted and soon realizes she's being watched - which is dangerous, considering she's hiding something from her husband. But each has secrets about what happened last year. And someone in this school will do anything to keep them silent"--
Includes reading group guide (pages [390]-391).
Keywords: Teenage girls -- Fiction; High school teachers -- Fiction; Teacher-student relationships -- Fiction; Secrecy -- Fiction; Scandals -- Fiction; Fiction; Suspense fiction